ANALISIS USAHA BUDIDAYA DAN PEMASARAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DI KECAMATAN NGALIYAN KOTA SEMARANG - Dewi Sekar tanjung; Lutfi Aris Sasongko; Shofia Nur Awami (Universitas Medan Area, 2018)
The objective of this research is to find out the amount of costs, income, and revenue from the cultivation and marketing of white oyster mushroom. The purposive sampling method was used for area determination. The sampling of white oyster mushroom farmers as respondents was carried out by census. Snowball technique was used for marketing institutions. The total respondents in this research were 34, consisting of 15 farmers, 5 collecting merchants, 4 retailers, and 10 end consumers. The analysis used was the cost analysis, revenue and income, marketing margin, farmer’s share and marketing efficiency. The results of this research are: the production cost in one peroid is Rp. 8.006.500; while farmer’s income is Rp. 16,588,800 per peroid; and the revenue received by the farmers is Rp. 8,880,900 per peroid. There are three types of marketing channels: Marketing Channel I, farmers directly sell to the consumers; Marketing Channel II, farmers sell via retailers, and subsequently continued toend consumers; Marketing Channel III, farmers sell to collecting merchants, and subsequently continued to retailers and end consumers. In Marketing Channel I, the farmers have a share value of 100%. In Marketing Channel II, the margin value is Rp. 2.100/kg, the total profit gained is Rp. 1.276/kg, with farmer’s share is 87.27%. Meanwhile, on Marketing Channel III, the margin value is Rp. 3.700/kg, with a profit gained of Rp. 2.086/kg, and the farmer’s share is 77.58%. The efficiency level in collecting merchants is 9.8%, and retailers at 4.5%. For efficiency level, the marketing of oyster mushroom through those three marketing channels is already efficient. Keywords: White Oyster Mushroom, Marketing Channels, Farmer’s Share, Marketing Efficiency